Adiponectin and cardiometabolic trait and mortality: where do we go?. Issue 9 (12th June 2021) - Jang, Albert Youngwoo; Scherer, Philipp E; Kim, Jang Young; Lim, Soo; Koh, Kwang Kon
Abstract: Adiponectin is an adipocyte-derived cytokine known for its cardioprotective effects in preclinical studies. Early epidemiologic studies replicated these findings and drew great interest. Subsequent large-scale prospective cohorts, however, showed that adiponectin levels seemed not to relate to incident coronary artery disease (CAD). Even more surprisingly, a paradoxical increase of all-cause and cardiovascular (CV) mortality with increased adiponectin levels was reported. The adiponectin-mortality paradox has been explained by some groups asserting that adiponectin secretion is promoted by elevated natriuretic peptides (NP). Other groups have proposed that adiponectin is elevated due to adiponectin resistance in subjects with metabolic syndrome or heart failure (HF). However, there is no unifying theory that can clearly explain this paradox. In patients with HF with reduced ejection fraction (HFrEF), stretched cardiomyocytes secrete NPs, which further promote release of adiponectin from adipose tissue, leading to adiponectin resistance. On the other hand, adiponectin biology may differ in patients with heart failure with preserved ejection fraction (HFpEF), which constitutes 50% of all of HF. Most HFpEF patients are obese, which exerts inflammation and myocardial stiffness, i.e. likely to prevent myocardial stretch and subsequent NP release. This segment of the patient population may display different adiponectin biology from its HFrEF counterpart. Dissecting the adiponectin-mortality relationship in terms of different HF subtypes may help to comprehensively understand this paradox. Mendelian randomization (MR) analyses claimed that adiponectin levels are not causally related to CAD or metabolic syndrome. Results from MR studies, however, should be interpreted with great caution because the underlying history of CAD or CHF was not taken into account in these analyses, an issue that may substantially confound the results. Here, we discuss many aspects of adiponectin; cardiometabolic traits, therapeutic interventions, and the ongoing debate about the adiponectin paradox, which were recently described in basic, epidemiologic, and clinical studies. Graphical Abstract: